Pathophysiology of Organs and Systems : Manual for the students of the 3rd course field of study 22 «Health Care» specialty 226 «Pharmacy, Industrial Pharmacy» educational qualification «Master of Pharmacy» professional qualification «Pharmacist» - Melnikova, O. V.; Grekova, T. A.; Ivanenko, T. V.; Kadzharyan, Y. V.; Danukalo, M. V.; Isachenko, M. I.; Мельнікова, Ольга Валеріївна; Грекова, Тетяна Анатоліївна; Іваненко, Тарас Васильович; Каджарян, Єлизавета Віталіївна; Данукало, Максим Вікторович; Ісаченко, Марія Ігорівна (Запорізький державний медико-фармацевтичний університет, 2023)
Pathophysiology is the most important subject in basic medical education. Pathophysiology is the study of the changes in body’s physiology that result from disease or injury. The professional activity of medical and pharmaceutical staff is aimed at preventing and treating diseases, therefore, comprehensive knowledge about disorders of organs and systems functioning and mechanisms of their diseases development is obligatory. The purpose of training the discipline "Pathophysiology" is to study general patterns and specific mechanisms of the occurrence, development, course and consequences of pathological processes, diseases themselves and pathological conditions. To do this, students must understand the importance of pathophysiology for medicine and the health care system, its place in the system of medical knowledge. It is important to be able to use knowledge of pathophysiology to analyze and assess the state of the body, disorders of the activity of organs and systems with the aim of further planning diagnostic studies, therapeutic and preventive measures. This Manual is based on many years of experience in teaching pathophysiology at the Zaporizhzhia State Medical University, as well as methodological materials for studying the subject in the system of higher medical education. The discipline program is structured into sections (logically completed parts of the curriculum), which include thematic sections represented by topics of practical classes. Wishing you success in Pathophysiology studying and hope that this knowledge will be useful to you in your future professional activities!